Reframing the link between metabolism and NLRP3 inflammasome: therapeutic opportunities - Ortega, Miguel A.; De Leon-Oliva, Diego; García-Montero, Cielo; Fraile-Martinez, Oscar; Boaru, Diego Liviu; de Castro, Amador Velazquez; Saez, Miguel A.; Lopez-Gonzalez, Laura; Bujan, Julia; Alvarez-Mon, Miguel Angel; García-Honduvilla, Natalio; Diaz-Pedrero, Raul; et al. (Frontiers in Immunology, 2023)
Inflammasomes are multiprotein signaling platforms in the cytosol that senses exogenous and endogenous danger signals and respond with the maturation and secretion of IL-1β and IL-18 and pyroptosis to induce inflammation and protect the host. The inflammasome best studied is the Nucleotide-binding oligomerization domain, leucine-rich repeatcontaining family pyrin domain containing 3 (NLRP3) inflammasome. It is activated in a two-step process: the priming and the activation, leading to sensor NLRP3 oligomerization and recruitment of both adaptor ASC and executioner pro-caspase 1, which is activated by cleavage. Moreover, NLRP3 inflammasome activation is regulated by posttranslational modifications, including ubiquitination/deubiquitination, phosphorylation/dephosphorylation, acetylation/deacetylation, SUMOylation and nitrosylation, and interaction with NLPR3 protein binding partners. Moreover, the connection between it and metabolism is receiving increasing attention in this field. In this review, we present the structure, functions, activation, and regulation of NLRP3, with special emphasis on regulation by mitochondrial dysfunction-mtROS production and metabolic signals, i.e., metabolites as well as enzymes. By understanding the regulation of NLRP3 inflammasome activation, specific inhibitors can be rationally designed for the treatment and prevention of various immune-or metabolic-based diseases. Lastly, we review current NLRP3 inflammasome inhibitors and their mechanism of action.